2012
DOI: 10.1017/thg.2012.23
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral Genetic Study of Humor Styles in an Australian Sample

Abstract: The present study investigated the extent to which individual differences in humor styles are attributable to genetic and/or environmental factors in an Australian sample. Participants were 934 same-sex pairs of adult twins from the Australian Twin Registry (546 monozygotic pairs, 388 dizygotic pairs) who completed the Humor Styles Questionnaire (HSQ). The HSQ measures four distinct styles of humor -affiliative, self-enhancing, aggressive, and self-defeating. Results revealed that additive genetic and non-shar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 17 publications
2
2
0
Order By: Relevance
“…The cartoons and captions were derived from the American based New Yorker magazine and thus the Canadian sample may have served as a surrogate for an American sample of participants. Conversely, Baughman and colleagues (2012) found an Australian twin sample produced results similar to those found in Britain in their study of self-reported humor styles. Although both Canada and Australia are members of the Commonwealth, Canada’s proximity to the United States and Australia’s relative geographical isolation may explain why Australian participants’ ratings of humor are more similar to British participants than to Canadian participants.…”
Section: Discussionsupporting
confidence: 58%
“…The cartoons and captions were derived from the American based New Yorker magazine and thus the Canadian sample may have served as a surrogate for an American sample of participants. Conversely, Baughman and colleagues (2012) found an Australian twin sample produced results similar to those found in Britain in their study of self-reported humor styles. Although both Canada and Australia are members of the Commonwealth, Canada’s proximity to the United States and Australia’s relative geographical isolation may explain why Australian participants’ ratings of humor are more similar to British participants than to Canadian participants.…”
Section: Discussionsupporting
confidence: 58%
“… Martin et al (2003) refined the item pool to measure the four humor styles using several samples to arrive at the final 32-item solution, the HSQ. Combining these samples ( N = 1,195), they obtained sufficient internal consistencies (Cronbach’s alpha ranging from .77 for aggressive to .81 for self-enhancing), which were replicated in other studies (e.g., Baughman et al, 2012 ). Occasionally, lower internal consistencies were obtained, especially in translated versions of the HSQ aggressive scale.…”
Section: Introductionsupporting
confidence: 67%
“…Effect sizes were small for affiliative, self-enhancing, and self-defeating (Cohen’s d < 0.20) and medium to large for aggressive (Cohen’s d = 0.72). Baughman et al (2012) replicated these gender differences. Others found significant gender differences (males obtaining higher values than females) for specific subscales only, namely for the aggressive scale (Cohen’s d = 0.39, Bilge & Saltuk, 2007 ; Cohen’s d = 0.43, Sirigatti et al, 2014 ) or the aggressive and self-defeating scales (Cohen’s d = 0.31 and 0.21, Kazarian & Martin, 2004 ).…”
Section: Introductionmentioning
confidence: 74%
“…This result is consistent with past research that has shown that men typically score lower than women on such variables as agreeableness across multiple cultures (e.g., Costa et al, 2001). This finding could also reflect gender differences in humor styles, as men tend to use aggressive humor more than women (e.g., Baughman et al, 2012). Finally, in the Polish sample, Item 5 (“Being mean to others can be exciting”) displayed moderate DIF favoring women.…”
Section: Discussionmentioning
confidence: 99%